2020
DOI: 10.1093/eurpub/ckaa166.577
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of using Cochrane systematic reviews by local HTA units

Abstract: The aim of this study is to evaluate the utilisation of CSRs by Quebec's local health technology assessment (HTA) units to promote efficiency in hospital decision-making. A survey was conducted using a structured online questionnaire to examine: Characteristics of the HTA units; Knowledge about works and services from the Cochrane Collaboration; Level of satisfaction about the use of CSRs; Facilitating factors and barriers to the implementation of CSRs evidence in a local context; Suggestions to improve the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For example, inclusion of certain items, particularly those related to 'contextualising findings' , may require additional work or expertise which some may consider to be outside the scope of a typical review [53]. However, these suggestions should not be ignored as research has shown that context is rarely provided in sufficient detail in existing reviews and guidelines [74], and applying evidence synthesis findings to local contexts is a major weakness reported by some health technology assessment (HTA) units trying to promote healthcare decisionmaking [75].…”
Section: Discussionmentioning
confidence: 99%
“…For example, inclusion of certain items, particularly those related to 'contextualising findings' , may require additional work or expertise which some may consider to be outside the scope of a typical review [53]. However, these suggestions should not be ignored as research has shown that context is rarely provided in sufficient detail in existing reviews and guidelines [74], and applying evidence synthesis findings to local contexts is a major weakness reported by some health technology assessment (HTA) units trying to promote healthcare decisionmaking [75].…”
Section: Discussionmentioning
confidence: 99%